Intraoperative oxygen tension and redox homeostasis in Pseudomyxoma peritonei: A short case series - Valenzuela-Molina, Francisca; Bura, Florina I.; Vázquez-Borrego, Mari C.; Granados-Rodríguez, Melissa; Rufián-Andujar, Blanca; Rufián-Peña, Sebastián; Casado-Adam, Ángela; Sánchez-Hidalgo, Juan Manuel; Rodríguez-Ortiz, Lidia; Ortega-Salas, Rosa; Martínez-López, Ana; Michán, Carmen; et al. (Frontiers in Oncology, 2023)
Pseudomyxoma peritonei (PMP) is a rare malignant disease characterized by a massive multifocal accumulation of mucin within the peritoneal cavity. The current treatment option is based on complete cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy. However, the recurrence is frequent with subsequent progression and death. To date, most of the studies published in PMP are related to histological and genomic analyses. Thus, the need for further studies unveiling the underlying PMP molecular mechanisms is urgent. In this regard, hypoxia and oxidative stress have been extensively related to tumoral pathologies, although their contribution to PMP has not been elucidated. In this manuscript, we have evaluated, for the first time, the intratumoral real-time oxygen microtension (pO2mt) in the tumor (soft and hard mucin) and surrounding healthy tissue from five PMP patients during surgery. In addition, we measured hypoxia (Hypoxia Inducible Factor-1a; HIF-1a) and oxidative stress (catalase; CAT) markers in soft and hard mucin from the same five PMP patient samples and in five control samples. The results showed low intratumoral oxygen levels, which were associated with increased HIF-1a protein levels, suggesting the presence of a hypoxic environment in these tumors. We also found a significant reduction in CAT activity levels in soft and hard mucin compared with healthy tissue samples. In conclusion, our study provides the first evidence of low intratumoral oxygen levels in PMP patients associated with hypoxia and oxidative stress markers. However, further investigation is required to understand the potential role of oxidative stress in PMP in order to find new therapeutic strategies.